Educação alimentar e nutricional: percepção de professores, coordenadores pedagógicos e nutricionistas - Nascimento, Vitor de Mattos [UNIFESP] (2016)
This study aims to understand and analyze the perception of teachers, coordinators, and nutritionists on their role in the process of food and nutrition education (FNE). This is a cross-sectional, descriptive study of qualitative and quantitative nature. Perceptions, concepts and practices of FNE of teachers (n=56) and coordinators (n=3) of two public elementary city schools of São Paulo (EMEFs), and nutritionists (n=28) of the School Feeding Department linked to the National School Feeding Programme were investigated using a Likert-type attitudinal instrument, narratives and semi-structured interviews, respectively. The Likert-type attitudinal instrument was built based on four dimensions and its validity was verified by linear correlation and reliability by applying the test of Wilcoxon signed rank. Results were described in mean values by assertions. Interviews and narratives were transcribed in verbatim and after that analyzed by using the content analysis method, from thematic nuclei. Categories and emerged from context and registry units. The study is in line with the ethical principles of research and authorization was granted by the Research Ethics Committee of the Federal University of São Paulo, under protocol number 1,242,853 of 09/24/2015. For teachers FNE actions must involve other professionals and areas of knowledge and should include in their conceptual base, the Nutrition and Food Security and the Human Right for an Adequate Nutrition themes. For coordinators FNE represents mainly the supply of food and its nutritional aspects. Nutritionists perceive the issue in different ways, especially FNE as a process that involves awareness raising and knowledge transfer aiming to achieve an eating behavior change. In the perception of teachers, coordinators, and nutritionists it can be observed the coexistence of different pedagogical trends, highlighting the traditional, as the more privileged models, as well as progressive models. These actors emphasized the need to develop interprofessional practices in FNE, and they consider important the presence of other areas of knowledge to guide these practices in school, as well as the need for permanent processes involving interdisciplinary and cross-content approaches.